2011
DOI: 10.1002/poc.1957
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic and stability studies on unsymmetrical 1,3‐dialkyl‐1,3‐diphosphacyclobutane‐2,4‐diyls

Abstract: Air-tolerant 2,4-bis(2,4,6-tri-t-butylphenyl)-1,3-diphosphacyclobutane-2,4-diyl singlet biradicals can be prepared by utilizing the unique reactivity of a kinetically stabilized PC triple bond compound. In this procedure, we studied the spectroscopic properties of a fundamental unsymmetrical P-heterocyclic biradical containing both PEt and PMe moieties, and the effects of the PCH 2 OMe group in relation to the stability of the P-heterocyclic biradical skeleton. The experimentally observed nuclear magnetic reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Until recently, all known cyclobutane-1,3-diyl derivatives incorporated equivalent radical centres, even though several examples investigated by the groups of Power and Yoshifuji are known featuring differing bridging moieties. 27 31 A synthetic protocol was devised by our group, enabling the synthesis of the formal group-15-substituted cyclobutanediyls [As(μ-NTer) 2 P] and [E 1 (μ-NTer) 2 E 2 ] (E 1 = N with E 2 = P, As, Sb; 1E 1 E 2 in Scheme 2 ). 32 , 33 The reactivity of singlet biradicaloids was mainly studied using the examples of diboradiphosphonio-cyclobutanediyls [ i Pr 2 P(μ-B t Bu)] 2 , 35 , 36 diphosphacyclobutane-diyls [ClC(μ-PMes*)] 2 (Mes* = 2,4,6-tri- tert butylphenyl), 37 , 38 diphosphadiazanediyls [P(μ-NTer)] 2 (Ter = 2,6-bis(2,4,6-trimethylphenyl)phenyl), 39 , 40 and digermynes R 2 Ge 2 (R = 2,6-bis(2,6-diisopropylphenyl)phenyl).…”
Section: Introductionmentioning
confidence: 99%
“…Until recently, all known cyclobutane-1,3-diyl derivatives incorporated equivalent radical centres, even though several examples investigated by the groups of Power and Yoshifuji are known featuring differing bridging moieties. 27 31 A synthetic protocol was devised by our group, enabling the synthesis of the formal group-15-substituted cyclobutanediyls [As(μ-NTer) 2 P] and [E 1 (μ-NTer) 2 E 2 ] (E 1 = N with E 2 = P, As, Sb; 1E 1 E 2 in Scheme 2 ). 32 , 33 The reactivity of singlet biradicaloids was mainly studied using the examples of diboradiphosphonio-cyclobutanediyls [ i Pr 2 P(μ-B t Bu)] 2 , 35 , 36 diphosphacyclobutane-diyls [ClC(μ-PMes*)] 2 (Mes* = 2,4,6-tri- tert butylphenyl), 37 , 38 diphosphadiazanediyls [P(μ-NTer)] 2 (Ter = 2,6-bis(2,4,6-trimethylphenyl)phenyl), 39 , 40 and digermynes R 2 Ge 2 (R = 2,6-bis(2,6-diisopropylphenyl)phenyl).…”
Section: Introductionmentioning
confidence: 99%
“…Compounds 6–8 were obtained by using arylmethyl bromide, whereas 9 and 10 were synthesized by the corresponding mesylate owing to the instability of the bromides. Table S1 summarizes the visible photoabsorption wavelengths of the transition from the highest occupied molecular orbital (HOMO) to the lowest unoccupied molecular orbital (LUMO) ( ϵ =700–1300) and the oxidation potentials . The visible photoabsorption and electron‐donating voltage were essentially unaffected by the aryl group.…”
Section: Resultsmentioning
confidence: 99%
“…The smaller pyramidalization of the t BuP phosphorus atom and shorter P( t Bu)–C1/C2 bonds would correlate with the electron‐donating character of the t ‐butyl group. The 31 P NMR spectroscopic data show the larger‐field chemical shift of the t BuP group,,,, which might be due to the canonical formula. The molecular structure of 8 indicated that the isopropylamino group increases the electron‐donating property of the P‐heterocyclic chromophore .…”
Section: Properties Of the Directly Arylated 13‐diphosphacyclobutanementioning
confidence: 99%
“…Positioning the sterically encumbered Mes* substituents is quite effective to stabilize the cyclic biradical (biradicaloid) skeleton, and handling of 1 in air at ambient temperatures is possible. The synthetic procedures of 1 including nucleophilic alkylation, acylation, and sulfanylation of the P‐heterocyclic anionic intermediates ( CBA ) was advantageous to afford a number of 1,3‐diphosphacyclobutane‐2,4‐diyls . Furthermore, the alkylation process was applicable to catenate the open‐shell singlet P‐heterocyclic units to construct the tetraradical and hexaradical derivatives showing the through‐space static interaction .…”
Section: Introductionmentioning
confidence: 99%